2014
DOI: 10.1039/c4gc00049h
|View full text |Cite
|
Sign up to set email alerts
|

Eco-efficient preparation of a N-doped graphene equivalent and its application to metal free selective oxidation reaction

Abstract: Here, we demonstrate that graphene oxide (GO) can be converted to N-doped reduced GO (rGO) that could become a substitute for N-doped graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The catalytic performance was evaluated using the model reaction between aniline and formic acid under an additive-free and solvothermal one-pot condition (140°C, 10 h), in comparison to mono-and tri-metallic catalysts (Table 1 and see ESI † Supplementary Table S4). Both monometallic Pd/N-rGO and commercial Pd/C catalysts produced a mixture of cyclohexanone and dicyclohexylamine via active hydrogenation, as expected (entries 1 and 2, Table 1), which was consistent with the reported results, [21][22][23][24][25] while a metal-free carbocatalyst (GO and N-rGO) 28,29 and mono-metals (Ag, Co, Au, Pt, Ni and Sn) loaded on N-rGO showed almost no catalytic effect (see ESI † entries 1-10, Supplementary Table S4). Positively, the Pd-based bimetallic nano-alloys with transition metals (Co, Au, Pt, Sn and Ni) produced N-methyl-N-phenylformamide (5) as a methylation product in a yield range of 18-70% (entries 3-7, Table 1).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The catalytic performance was evaluated using the model reaction between aniline and formic acid under an additive-free and solvothermal one-pot condition (140°C, 10 h), in comparison to mono-and tri-metallic catalysts (Table 1 and see ESI † Supplementary Table S4). Both monometallic Pd/N-rGO and commercial Pd/C catalysts produced a mixture of cyclohexanone and dicyclohexylamine via active hydrogenation, as expected (entries 1 and 2, Table 1), which was consistent with the reported results, [21][22][23][24][25] while a metal-free carbocatalyst (GO and N-rGO) 28,29 and mono-metals (Ag, Co, Au, Pt, Ni and Sn) loaded on N-rGO showed almost no catalytic effect (see ESI † entries 1-10, Supplementary Table S4). Positively, the Pd-based bimetallic nano-alloys with transition metals (Co, Au, Pt, Sn and Ni) produced N-methyl-N-phenylformamide (5) as a methylation product in a yield range of 18-70% (entries 3-7, Table 1).…”
Section: Resultssupporting
confidence: 80%
“…Three N1s peaks at~399, 400 and 402 eV were assigned to the pyridinic, pyrolic and graphitic or quaternary N (see ESI † Supplementary Figure S4c). 28,29,31 The large amount of nitrogen (~4 at %) and oxygen atoms (~18 at %) in Supplementary Table S5 coordinated metal NPs on the graphene in a well dispersed and stable manner, preventing the re-oxidation of noble metal M 0 (M = Ag, Pd), as reported for N-doped carbon. 15,32 Therefore, a structural model of Pd 47 Ag 53 /Fe 3 O 4 /N-rGO could be hypothetically proposed (in ESI † Supplementary Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Kim and co‐workers, N‐doped graphene containing 6.3 at. % of nitrogen successfully oxidized benzyl alcohol, benzyl bromides and styrene to the corresponding aromatic acid products by a free‐radical mechanism with tert ‐butyl hydroperoxide (TBHP) as oxidant 19. The addition of methanol furnished aromatic esters.…”
Section: Cmgs As Carbocatalystsmentioning
confidence: 99%
“…Metal-free boron-doped graphene exhibited a good electrocatalytic activity toward oxygen reduction reaction in alkaline solutions for fuel cells [25,[30][31][32]. Nitrogen-doped graphene, with and without metal/metal oxide nanoparticles, also displayed good electrocatalytic activities toward oxygen reduction reaction [25][26][27][28][29][30]. However, metal-free nitrogen-doped graphene was used to fabricate the electrochemical sensor for simultaneous determination of ascorbic acid, dopamine, and uric acid in neutral aqueous solutions [33].…”
Section: Introductionmentioning
confidence: 97%
“…A variety of graphene or reduced graphene oxide (rGO)-based electrochemical sensors, decorated with precious metal nanoparticles (Au [14], Pd [15], and Au-Pd [16]), metal/transition metal oxide nanoparticles (K [17], ZnO [18], Fe 2 O 3 [19], Fe 3 O 4 [20], Co 3 O 4 [21]), metalloproteins (hemoglobin [22] and myoglobin [23]), and polyelectrolytes (poly(diallyldimethylammonium chloride), PDDA [24]) have been fabricated toward oxidation of nitrite. In recent years, it has been shown that the electronic property, chemical activity, and optical characteristics of graphene can be tailored by chemical doping with heteroatoms such as boron and nitrogen [25][26][27][28][29][30][31][32]. It is highly desirable to develop non-precious metal or even metal-free electrocatalysts with excellent catalytic performances because of low cost, long-term stability, and resistance to catalyst poisoning.…”
Section: Introductionmentioning
confidence: 99%